Stiff-man syndrome: identification of 17β-hydroxysteroid dehydrogenase type 4 as a novel 80-kDa antineuronal antigen - Dinkel, Klaus; Rickert, Mathias; Möller, Gabriele; Adamski, Jerzy; Meinck, Hans-Michael; Richter, Wiltrud (Journal of neuroimmunology, 2002)
Stiff-man syndrome (SMS) is a rare autoimmune disorder of the central nervous system associated with autoantibodies to glutamate decarboxylase (GAD). We isolated five brain-reactive human monoclonal antibodies, with reactivity distinct from GAD, from peripheral blood of a patient newly diagnosed with SMS. Two antibodies reacted with both Purkinje cells and ependymal cells, and precipitated an 80-kDa protein from rat neuronal primary cultures, which was also recognized by 12% (3/25) of SMS sera and 13% (2/15) of SMS cerebrospinal fluid (CSF) samples. The corresponding antigen was identified as 17β-hydroxysteroid dehydrogenase type 4 and may represent a possible novel target of autoimmunity in SMS.
Gesehen am 01.03.2021